2005
DOI: 10.1143/jjap.44.2525
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Extraction Efficiency of GaN-Based Light-Emitting Diodes with Textured Surface Layer by Natural Lithography

Abstract: In this study, p-side-up GaN-based light-emitting diodes (LEDs) with textured indium-tin oxide (ITO) or silicon dioxide (SiO 2 ) surface layers were investigated by natural lithography using polystyrene spheres (PSs) as an etching mask. It was found that the ITO top layer provides better roughness than SiO 2 . Under the optimum surface treatment parameter, the roughnesses of textured ITO and SiO 2 surface layers are 140 nm and 15 nm, respectively. The diameter of PSs in the textured ITO surface is still mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…[5][6][7][8][9] It has been shown that one could construct the GaN surface so that photons can escape easily thus enhancing the LED out-put intensity. [10,11] It is also possible to improve the brightness of the GaN-based LED by fabricating oblique sidewalls. Gao et al [12] reported on the extraction efficiency enhancement by nano-roughened p-GaN surface.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] It has been shown that one could construct the GaN surface so that photons can escape easily thus enhancing the LED out-put intensity. [10,11] It is also possible to improve the brightness of the GaN-based LED by fabricating oblique sidewalls. Gao et al [12] reported on the extraction efficiency enhancement by nano-roughened p-GaN surface.…”
Section: Introductionmentioning
confidence: 99%
“…Textured surface technique became popular in order to avoid the problem that external quantum efficiency is limited by the total internal reflection of emitting light at interface of semiconductor and air due to large difference of refractive index (Yang et al 2005). To form surface texture pattern, several techniques are applied, such as anisotropic photoelectrochemical etching process (Fujii et al 2004), natural lithography (Yang et al 2005).…”
mentioning
confidence: 99%
“…Textured surface technique became popular in order to avoid the problem that external quantum efficiency is limited by the total internal reflection of emitting light at interface of semiconductor and air due to large difference of refractive index (Yang et al 2005). To form surface texture pattern, several techniques are applied, such as anisotropic photoelectrochemical etching process (Fujii et al 2004), natural lithography (Yang et al 2005). These techniques make LED surface roughened in shape of trapezia (Han et al 2006), pyramid (Fujii et al 2004) and V-shaped (Tsai et al 2006), Surface roughness is critical and must be controlled by about one-half wavelength according to (Yang et al 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation